Challenges in maintaining the probiotic potential in alcoholic beverage development - Santos, Daiane Costa dos; Oliveira Filho, Josemar Gonçalves de [UNESP]; Andretta, Juliana Risso; Silva, Fabiano Guimarães; Egea, Mariana Buranelo (Elsevier, 2023)
The development of new functional alcoholic beverages to promote health benefits is a major challenge for current research. This review presents the main applications of microorganisms with functional potential and resistant to the alcoholic environment as well as the characteristics that enable the use of alcoholic beverages as vehicles for probiotic microorganisms. In our online search, it was possible to notice that the most prominent microorganisms with functional potential and that present alcohol resistance were Saccharomyces cerevisiae var. boulardii and water-kefir (composed of Saccharomyces sp., Lactobacillus sp., Leuconostoc sp., Acetobacter sp., Bifidobacterium sp.). Processing conditions, temperature, fermentation time, and raw materials used in the production of beverages are important parameters that are evaluated and are dependent on the alcohol concentration and cellular viability of the desired probiotic microorganism(s). Viability studies of probiotic microorganisms in vegetable matrices have been conducted for water-kefir and Saccharomyces boulardii. S. boulardii was successfully incorporated into the developmental process of alcoholic beverages with alcohol contents ranging from 3.83 to 23% (v/v), whereas kefir beverage had an alcohol content ranging from 0.8 to 4.96% (v/v). Furthermore, to ensure the maintenance of probiotic viability in alcoholic matrices, the encapsulation technique can be used as an alternative to promote greater protection and viability of probiotics against adverse conditions.
Keywords: Alcohol concentration; Functional beverage; Microbiological resistance